Communication of innovations : a journey with EV Rogers - Singhal, Arvind (ed.); Dearing, James W. (ed.) (New Delhi, 2006)
This collection of 10 original essays honors the intellectual legacy of Prof Everett M Rogers (1931-2004), a pioneering and distinguished teacher$1 (Bscholar of diffusion of innovations, communication networks, and social change. Well-known colleagues and contemporaries write on topics that not only piqued Rogers$1 (Bcuriosity, but to which he made seminal and lasting contributions. The concluding chapter documents Rogers$1 (Blife journey from his modest farm boy beginnings in Iowa, through his distinguished academic career, to his final return to the farm.s
Keywords: Communication